2007
DOI: 10.1038/sj.bmt.1705720
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of caspofungin as secondary prophylaxis in patients undergoing allogeneic stem cell transplantation with prior pulmonary and/or systemic fungal infection

Abstract: Transplanted patients with a history of invasive fungal infection (IFI) are at high risk of developing relapse and fatal complications. Eighteen patients affected by hematological malignancies and a previous IFI were submitted to allogeneic stem cell transplantation, using Caspofungin as a secondary prophylaxis. Patients had a probable or proven fungal infection and 16 had a pulmonary localization. No side effects were recorded during treatment with Caspofungin. Compared to pre-transplant evaluation, stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Most of the previous studies regarding secondary prophylaxis in patients with hematological malignancies are retrospective and include small heterogenous patients' populations, with various IMI classifications and different responses to antifungal treatment before HSCT. [2][3][4][5][6][7][8] Nonetheless, studies in which secondary prophylaxis was amphotericin B or first-generation triazoles reported commonly significant rates of relapsed IMIs (29-33%) and associated mortality rates (88%) in patients with hematological malignancies and histories of IMIs before allogeneic HSCT; 2-4 of note, liposomal amphotericin B was also shown to be associated with a high rate of kidney injury (36%). 4 In addition, other investigators described conflicting results about the efficacy of secondary prophylaxis with echinocandins with a wide range of IMI relapse (11-32%).…”
mentioning
confidence: 99%
“…Most of the previous studies regarding secondary prophylaxis in patients with hematological malignancies are retrospective and include small heterogenous patients' populations, with various IMI classifications and different responses to antifungal treatment before HSCT. [2][3][4][5][6][7][8] Nonetheless, studies in which secondary prophylaxis was amphotericin B or first-generation triazoles reported commonly significant rates of relapsed IMIs (29-33%) and associated mortality rates (88%) in patients with hematological malignancies and histories of IMIs before allogeneic HSCT; 2-4 of note, liposomal amphotericin B was also shown to be associated with a high rate of kidney injury (36%). 4 In addition, other investigators described conflicting results about the efficacy of secondary prophylaxis with echinocandins with a wide range of IMI relapse (11-32%).…”
mentioning
confidence: 99%
“…[7][8][9]11,12 Our experience in the treatment and prophylaxis of IFI confirmed the efficacy of the above agents. In January 2001, we introduced itraconazole and amphotericin B into the secondary prophylaxis of IFI during HSCT.…”
Section: Introductionmentioning
confidence: 52%
“…Our study showed a relatively low rate of IFI-related mortality in comparison with earlier studies. [4][5][6][7][8][9] This should be dedicated to the high active secondary prophylaxis, for most of our patients (95.9%, 47/49) received broad-spectrum antifungal agents. [7][8][9] The low proportion (10.2%, 5/49) of proven cases of historical IFI may explain the difference between our results and the literature, which reflects the higher severity of infection in Days after transplantation Figure 1 Cumulative incidence of failure of prophylaxis in patients with versus without residual diseases before transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations